2010
DOI: 10.1016/j.physletb.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Quantum Hall Effect from type IIA string theory on the K3 surface

Abstract: Using D-brane configurations on the K3 surface, we give six dimensional type IIA stringy realizations of the Quantum Hall Effect (QHE) in 1+2 dimensions. Based on the vertical and horizontal lines of the K3 Hodge diamond, we engineer two different stringy realizations.The vertical line presents a realization in terms of D2 and D6-branes wrapping the K3 surface. The horizontal one is associated with hierarchical stringy descriptions obtained from a quiver gauge theory living on a stack of D4-branes wrapping int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Although theories with holographic duals can be microscopically very different to a typical condensed system, their long wavelength behavior can be similar and be used as a playing ground to understand better the properties of FQH states. Indeed, there have been many proposals at describing QH states using holography [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Although some of these models describe fractional filling fractions and features like transitions between Hall plateaus, the situation is not entirely satisfactory when the holographic models are examined in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Although theories with holographic duals can be microscopically very different to a typical condensed system, their long wavelength behavior can be similar and be used as a playing ground to understand better the properties of FQH states. Indeed, there have been many proposals at describing QH states using holography [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Although some of these models describe fractional filling fractions and features like transitions between Hall plateaus, the situation is not entirely satisfactory when the holographic models are examined in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that the Susskind model can be constructed by a ten dimensional system of D0, D2 and D6-branes and F1 strings stretched between the D2 and D6-branes [2]. Using D-brane configurations on the K3 surface, a six dimensional type IIA stringy realization of these type of models, has been given in terms of D2 and D6-branes wrapping the K3 surface [8].…”
Section: Introductionmentioning
confidence: 99%
“…We refer to this as the (gravity) bulk. 5 Holographic models of the quantum Hall effect have also been studied in [6,7,8,9,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Here, Γ 0 (2) is a subgroup of SL(2, Z) and is generated using two elements ST 2 S and T . 8 Note that Γ 0 (2) does not include the single S-operation of SL(2, Z) in its elements. In the context of the AdS/CFT correspondence, it was found in [11,12] that the d = 4 axio-dilaton gravity with SL(2, Z) symmetry provides a holographic model of the mentioned duality transformation (1.1)-(1.3) in the quantum Hall effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation